Distribution of Second Primary Malignancies Suggests a Bidirectional Effect Between Breast and Endometrial Cancer: A Population-Based Study. Issue 8 (1st November 2009) - Cortesi, Laura; De Matteis, Elisabetta; Rashid, Ivan; Cirilli, Claudia; Proietto, Manuela; Rivasi, Francesco; Federico, Massimo
Abstract : Introduction: The aim of this study was to investigate the incidence of second primary tumors in patients with breast cancer (BC), with particular regard to bidirectional risk for endometrial cancer (EC). Methods: A total of 7512 and 343 patients with first and second primary BC, respectively, were referenced to the expected number of cases calculated using the standardized incidence ratio (SIR) over the same period, to evaluate the observed and expected ratio between the groups. Data on tamoxifen use were also considered. Results: A total of 499 women with primary BC developed a second tumor. The total SIR, that is, the ratio between observed second primary cancer among patients with BC and the expected primary cancers in the general population, was significantly higher (SIR = 1.23; 95% confidence interval, 1.12-1.34; P = 0.007), particularly for melanoma (2.25), EC (2.15), ovarian cancer (1.74), hematologic malignancies (1.36), and bilateral BC (1.25). A greater risk of BC after thyroid (2.22) and EC (1.62) was also observed. Furthermore, the risk of developing EC was higher in patients treated with tamoxifen (SIR = 2.50 vs 1.34). Conclusions: Bidirectional risk of endometrial cancer was not exclusively related to tamoxifen use.